DEVELOPING A THEORETICAL SERVICE QUALITY FRAMEWORK FOR A STUDENT FUNDING SYSTEM - Riaan Dirkse van Schalkwyk; Sumei van Antwerpen (Program Studi Manajemen Pendidikan, 2025)
This article proposes a comprehensive theoretical framework aimed at enhancing service quality (SQ) within a student funding system in South Africa. Drawing on extensive literature regarding SQ and organisational excellence, the framework integrates macro-level systemic dimensions with micro-level student-focused components. The study employed a qualitative research methodology, incorporating a document analysis approach as primary data collection techniques. This approach emphasises a holistic strategy for the re-engineering of a student funding system, aligning with stakeholder needs and the Baldrige Performance Excellence Framework. Key dimensions identified within this framework leadership, strategic planning, operational processes, stakeholder engagement, continuous improvement, and measurement are essential for achieving superior service delivery and organisational effectiveness. The findings suggest that this theoretical framework not only addresses existing gaps in student funding operations but also sets the foundation for future empirical validation and refinement.